Institutions and Governance of Subak in the Development of Sustainable Ecotourism - Supranoto, Supranoto; Candranegara, I Made Wimas (Indonesian Association for Public Administration (IAPA), 2024)
This research discusses Subak as an irrigation system that irrigates rice fields to produce food, especially rice, which is the staple food of the community. Subak is always carried out together with religious ceremonies and has noble values ​​related to the concept of Tri Hita Karana. The Tabanan Regency Government is trying to develop tourism but still maintains the existence of subak by combining these two things into a new tourist attraction. The attraction that can be developed by combining tourism with agriculture is through the concept of ecotourism. One of these government programs is the Subak Lestari program. The findings of problems in the field faced by Subak Celemanik to be developed as an ecotourism area are that tourist attractions with a subak background have not been managed as the main attraction but tend to be as supporting tourism in Kerambitan District, the variety of tourist attractions offered is still small, the lack of subak's ability to provide supporting facilities, land conversion because it is considered property rights, the absence of local tour guides, and the absence of extensive subak marketing. The urgency of this research is carried out considering the massive development of tourism in Bali, resulting in rice fields, especially subak, starting to change function into tourist accommodation. The method used in this study is qualitative using SWOT analysis. The results of this study are that it is necessary to maximize the performance of the Subak management institution in establishing cooperation with the government or related stakeholders, increasing the participation of Subak members in supervising the implementation of customary laws and regulations.